2018
DOI: 10.7759/cureus.2494
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Difference in Post-procedural Stroke Rates Between Patients with Aortic Stenosis Who Undergo Transcatheter Aortic Valve Replacement Versus Surgical Aortic Valve Replacement

Abstract: Transcatheter aortic valve replacement (TAVR) is a newer alternative to surgical aortic valve replacement (SAVR) for patients with severe aortic stenosis. Clinical trials have investigated TAVR's safety and effectiveness. Cerebral embolization is a common complication leading to stroke after TAVR and SAVR; different cerebral protection methods have been studied to prevent this.This paper evaluates the rate of post-procedural stroke rates between TAVR and SAVR and investigates the effect of cerebral protective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…Transcatheter aortic valve replacement is the standard treatment of choice at present for aortic stenosis. 4 One of the major complications includes stroke. The rate of incidence of stroke is much higher in surgically treated aortic stenosis than TAVI.…”
Section: Discussionmentioning
confidence: 99%
“…Transcatheter aortic valve replacement is the standard treatment of choice at present for aortic stenosis. 4 One of the major complications includes stroke. The rate of incidence of stroke is much higher in surgically treated aortic stenosis than TAVI.…”
Section: Discussionmentioning
confidence: 99%
“…22 Recent comparisons find similar, or slightly lower stroke risk with TAVI versus SAVR (Supplementary Tables 2 and 4). Cerebral embolic protection devices will improve TAVI neurological outcomes, 23 albeit at increased expense, and recent trials demonstrate both minimal effect, and 50% reduction in cerebral lesions. 23…”
Section: Pacemaker Implantationmentioning
confidence: 99%
“…Cerebral embolic protection devices will improve TAVI neurological outcomes, 23 albeit at increased expense, and recent trials demonstrate both minimal effect, and 50% reduction in cerebral lesions. 23…”
Section: Pacemaker Implantationmentioning
confidence: 99%
“…[3,4] Despite the amelioration in technique and technology of TAVR, questions remain related to the safety and effi cacy of this procedure, especially regarding to the complications that follow TAVR. [5][6][7][8] Silent ischemic cerebral infarction is one of the major concerns that have been associated with TAVR. Previous studies reported as high as 58%-91% of new silent ischemic stroke detected by diffusion-weighted magnetic resonance imaging (DW-MRI) occurred following TAVR.…”
Section: Introductionmentioning
confidence: 99%